2022
DOI: 10.1111/iej.13819
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces inflammation in rat apical periodontitis

Abstract: Aim The aim of the study was to evaluate the effect of systemic curcumin administration on the severity of apical periodontitis (AP). Methodology Forty male Wistar rats weighing 250–280 g each, age 2.5 months, were distributed into four groups (n = 10): control untreated rats (C), control rats treated with curcumin (CUR), rats with pulp exposure‐induced apical periodontitis (AP) and rats with pulp exposure‐induced apical periodontitis treated with curcumin (AP‐CUR). Curcumin treatment was administered orally o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Curcumin is a potent antioxidant that facilitates mitochondrial activities, reduces the level of ROS and lipid peroxidation, improves SOD activity and inhibits erastin-induced ferroptosis [ 40 , 41 ]. Many studies have shown that curcumin has a potential role in the treatment of periodontitis [ 42 , 43 ]. However, the exact mechanism of curcumin in ligature-induced periodontitis has not been studied clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin is a potent antioxidant that facilitates mitochondrial activities, reduces the level of ROS and lipid peroxidation, improves SOD activity and inhibits erastin-induced ferroptosis [ 40 , 41 ]. Many studies have shown that curcumin has a potential role in the treatment of periodontitis [ 42 , 43 ]. However, the exact mechanism of curcumin in ligature-induced periodontitis has not been studied clearly.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a histological and histometric evaluation was performed to understand the signaling pathways and mediators involved in bone resorption. This method is commonly used to determine periapical bone loss in induced apical periodontitis [ 10 , 12 ] but this analysis could be improved through tomographic volumetric measurements [ 36 38 ]. This is one limitation of the present study, which should be better explored in future studies.…”
Section: Discussionmentioning
confidence: 99%